COVID-19 patients with coronary artery disease have a higher mortality risk: a meta-analysis. (14th October 2021) - Zuin, M; Rigatelli, G; Zuliani, G; Roncon, L
Abstract: Background: The prevalence and prognostic implications of coronary artery disease (CAD) in patients infected by the novel coronavirus 2019 disease (COVID-19) remain unclear. Purposes: We conducted a systematic review and meta-analysis to investigate the prevalence and mortality risk in COVID-19 patients with pre-existing CAD. PRISMA. guidelines were followed in abstracting data and assessing validity. We searched Medline, Scopus and Web of Science to locate all articles published up to December 8, 2020 reporting data of COVID-19 survivors and non-survivors with pre-existing CAD. Data were pooled using the Mantel-Haenszel random effects models with odds ratio (OR) as the effect measure with the related 95% confidence interval (CI). Statistical heterogeneity between groups was measured using the Higgins I 2 statistic. Results: Twenty-four studies, enrolling 22744 patients [mean age 58.2 and 70.9 years for survivors and non-survivors (p<0.0001), respectively], met the inclusion criteria and were included into the final analysis. The pooled prevalence of pre-existing CAD in COVID-19 patients was 11.5% (95% CI 0.097–0.136) and resulted significantly higher in non-survivors compared to survivors (16.7% vs 7.1%, respectively, p<0.0001). A random-effect model confirmed a significant higher risk of death in COVID- 19 patients with pre-existing CAD in the short-term period (OR 2.96, 95% CI 2.18–4.03, p<0.0001, I 2 =79%) (Figure 1). A meta-regression, using age as moderator, did not identify any statistical significance (Coeff: −0.046, 95% CI −0.101–0.009, p=0.104). The Egger's regression test (t=0.596; p=0.06) confirmed that there were not statistically evidences of publication bias Conclusions: Pre-existing CAD in COVID-19 patients significantly increased the risk of death during the infection. FUNDunding Acknowledgement: Type of funding sources: None.